Review of Islamic Law on The Musaqah System of Rubber Gardens in Betung Village, Lubuk Keliat Ogan Ilir District - Saprida Saprida; Choiriyah Choiriyah; Emilia Sari (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
Musaqah is a form of cooperation between garden owners and farmers. The goal is that the garden is maintained and cared for, so as to provide maximum results. Everything produced by the second party in the form of fruits is a joint right between the owner and the tenant in accordance with the agreement made. The profit-sharing system carried out in Betung village, Lubuk Keliat sub-district is by agreement that adheres to a musaqah contract. This kind of cooperation agreement has long been practiced by the Betung village community, namely the owner of the handover garden of a rubber plantation to be cultivated and managed by local farmers with the provisions that the garden produce in the form of rubber latex is sold and the money is divided between the two parties according to the agreement, which is divided into three parts, one part for rubber tappers, two parts for rubber garden owners. The review of Islamic law regarding the profit-sharing system in Betung Village, Lubuk Keliat District is in accordance with the pillars and conditions of musaqah in Islam, where the garden owner and rubber tappers make an agreement at the beginning.Keywords: Islamic Law, Akad, Musaqah. AbstrakMusaqah merupakan bentuk kerjasama antara pemilik kebun dan petani. Tujuannya agar kebun dipelihara dan dirawat, sehingga memberikan hasil yang maksimal. Segala sesuatu yang dihasilkan oleh pihak kedua berupa buah-buahan merupakan hak bersama antara pemilik dan penyewa sesuai dengan kesepakatan yang dibuat. Sistem bagi hasil yang dilakukan di desa Betung kecamatan Lubuk Keliat adalah dengan kesepakatan yang menganut akad musaqah. Akad kerjasama semacam ini sudah lama dipraktikkan oleh masyarakat desa Betung yaitu pemilik kebun serah terima sebidang kebun karet untuk diusahakan dan dikelola oleh petani setempat dengan ketentuan hasil kebun berupa getah karet dijual dan uangnya dibagi antara kedua belah pihak sesuai kesepakatan, yaitu dibagi menjadi tiga bagian, satu bagian untuk penyadap karet, dua bagian untuk pemilik kebun karet. Tinjauan syariat Islam tentang sistem bagi hasil di Desa Betung Kecamatan Lubuk Keliat sudah sesuai dengan rukun dan syarat musaqah dalam Islam, dimana pemilik kebun dan penyadap Karet membuat kesepakatan di awal.Kata Kunci: Hukum Islam, Akad, Musaqah.